Music and mind - Jahnichen, Gisa (Universiti Putra Malaysia Press, 2014)
This volume is dedicated to the topic MUSIC & MIND. Sub themes were music and cognitive processes of perception and music therapy among others. Other fields included social, political, and religious discourses that influence mindsets on status, cultural positioning and the significance of the individual as expressed through music. Some contributors explored music and individual preference in distinctive communities. Finally, aesthetics of music were discussed in philosophical and scientific approaches to musical meanings